2004
DOI: 10.1074/jbc.m408920200
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Function of Mitochondrial Uncoupling Protein in Plants

Abstract: Plant mitochondrial uncoupling protein (UCP) is activated by superoxide suggesting that it may function to minimize mitochondrial reactive oxygen species (ROS) formation. However, the precise mechanism of superoxide activation and the exact function of UCP in plants are not known. We demonstrate that 4-hydroxy-2-nonenal (HNE), a product of lipid peroxidation, and a structurally related compound, trans-retinal, stimulate a proton conductance in potato mitochondria that is inhibitable by GTP (a characteristic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 30 publications
9
98
0
2
Order By: Relevance
“…In animal mitochondria, the products of lipid peroxidation that arise from ROS, such as HNE and the structurally related compounds trans-retinoic acid, trans-retinal and other 2-alkenals, specifically induce the uncoupling of mitochondria through the uncoupling proteins UCP2 and UCP3 (Rial et al 1999;Echtay et al 2003). Similarly, the induction of mitochondrial uncoupling by HNE and trans-retinal has been observed in plant mitochondria (Smith et al 2004). Moreover, it has been shown that exogenously generated superoxide activates UCPs in both animal and plant mitochondria in the presence of FFAs (Considine et al 2003;Echtay et al 2002a).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In animal mitochondria, the products of lipid peroxidation that arise from ROS, such as HNE and the structurally related compounds trans-retinoic acid, trans-retinal and other 2-alkenals, specifically induce the uncoupling of mitochondria through the uncoupling proteins UCP2 and UCP3 (Rial et al 1999;Echtay et al 2003). Similarly, the induction of mitochondrial uncoupling by HNE and trans-retinal has been observed in plant mitochondria (Smith et al 2004). Moreover, it has been shown that exogenously generated superoxide activates UCPs in both animal and plant mitochondria in the presence of FFAs (Considine et al 2003;Echtay et al 2002a).…”
Section: Introductionmentioning
confidence: 89%
“…Our results indicated that HNE induced the AcUCP-mediated proton conductance both in non-phophorylating and phosphorylating mitochondria, decreasing the yield of oxidative phosphorylation in the latter. Therefore, we can conclude that activation by alkenal lipid peroxidation products also affects the UCPs of unicellular organisms, such as that of protozoan A. castellanii, similar to plant (Smith et al 2004) and mammalian UCPs . In mammalian and plant mitochondria, the stimulation of UCPs by physiologically relevant concentrations of HNE and FFAs (Kowaltowski et al 1998) decreases mitochondrial ROS generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this deficiency in the proton gradient, plants have a strategy developed from uncoupling proteins (UCP) embedded in the inner mitochondrial membrane (Smith et al, 2004;ArnholdtSchmitt et al, 2006). Uncoupling proteins activity can enhance the transfer of protons into the mitochondria by controlling the rate of production of superoxides, and may even have some control over the TCA cycle, because increases in the UCP content can increase the rate of conversion of pyruvate to citrate (Smith et al, 2004).…”
Section: Oxidative Phosphorylation In Plantsmentioning
confidence: 99%
“…Furthermore, alternatives have also been found to the maintenance of the proton gradient in the mitochondrial matrix, which is performed through uncoupled proteins (UCP) that enables flows of protons to enter the matrix independent of ATP synthesis (ArnholdtSchmitt et al, 2006). In turn, UCP would participate in the reduction of reactive oxygen species (ROS), a function also contributed to by AOX (Smith et al, 2004).…”
Section: Introductionmentioning
confidence: 99%